UV‑C irradiation as an alternative treatment technique: Study of its effect on microbial inactivation, cytotoxicity, and sensory properties in cranberry-flavored water. (March 2019) - Gopisetty, Vybhav Vipul Sudhir; Patras, Ankit; Pendyala, Brahmaiah; Kilonzo-Nthenge, Agnes; Ravi, Ramasamy; Pokharel, Bharat; Zhang, Lijuan; Si, Hongwei; Sasges, Michael
Abstract: The impact of UV‑C irradiation at 254 nm on microbial inactivation, cytotoxicity, and sensory properties of cranberry-flavored water (CFW) was studied using a continuous flow-through system. Two different bacterial outbreak strains, Escherichia coli ATCC 700728 and Salmonella enterica serovar Muenchen ATCC BAA 1764, were inactivated by >5 log10 CFU/mL at an UV‑C fluence of 12 mJ·cm −2 and 16 mJ·cm − 2 from an initial concentration of approximately 8 log CFU·mL −1 with D values of 2.11 and 3.14 mJ·cm − 2, respectively. Cytotoxicity evaluation of CFW in human endothelial cells (EA.hy926) demonstrated no toxic effects up to a maximum delivered UV‑C fluence of 120 mJ·cm − 2 . Quantitative Descriptive Analysis (QDA) was performed to evaluate the sensory attributes of UV‑C irradiated CFW at two (30 and 120 mJ·cm − 2 ) UV‑C fluence levels. Our results suggested that UV‑C irradiated CFW had no significant difference ( p  > 0.05) in sensory attributes up to a fluence of 30 mJ·cm − 2 which is below the FDA-recommended UV‑C fluence (40 mJ·cm − 2 ) for the inactivation of E. coli and Salmonella . Overall, this research suggests that UV‑C treatment of CFW can achieve effective microbial inactivation, without the generation of cytotoxic effects, and also can retain its sensory attributes. These results demonstrated that UV‑C irradiation can be an alternative treatment technique in processing of beverages while maintaining food safety and quality. Highlights: UV‑C irradiation reduced the microbial load in cranberry-flavored water by 5-log cycles. UV‑C retained all the measured sensory attributes up to a fluence of 30 mJ·cm − 2 . UV‑C irradiation did not produce cytotoxic compounds in cranberry-flavored water. UV‑C irradiation can be used in the processing of beverages, ensuring food quality and safety.